Intravitreal Injections of Bevacizumab (Avastin); which Dose is Recommended? - Yasmena Abdulhadi; Bahjah Abdulhamid Esehiyb (Khalij-Libya Journal of Dental and Medical Research, 2024)
This study was conducted to evaluate the fast improvement, effectiveness & safety of intravitreal injections bevacizumab (Avastin), in different doses, for treating diabetic macular edema (DME). Eyes of 80 patients with diabetic macular edema were randomized and planned to receive three consecutive monthly intravitreal injections of 1.25 mg or 2.5 mg bevacizumab (forty patients for each group). Patients were observed for 4 weeks after 1st injection and the changes in the best-corrected visual acuity (BCVA), central macular thickness (CMT) and adverse events were compared between both groups. CMT was significantly reduced in both groups (P < 0.013). Significant improvements between baseline and 2weeks to 4weeks in the 2.5 mg group, were mean decrease in CMT was 318 t0 182(P<.001), mean BCVA is 0.16 improve to 0.7 and P value 0.001. Intraocular pressure (IOP)measurements post intravitreal (IV) bevacizumab injection was not raised its statistically significant (P < 0.001). CMT improvement with a dose of intravitreal IV injection 2.5 mg is promising a rapid safe effective response for treating DME without any ocular or systemic side effects but Follow-up is still short to make any specific treatment recommendations. أجريت هذه الدراسة لتقييم التحسن السريع والفعالية والسلامة لحقن عقار بيفاسيزوماب (أفاستين) داخل الجسم الزجاجي بجرعات مختلفة لعلاج الوذمة البقعية السكرية (DME). تم اختيار عيون 80 مريضاً يعانون من الوذمة البقعية السكرية بشكل عشوائي وتم التخطيط لتلقي ثلاث جرعات متتالية من العقار جرعو واحدة للمدة ثلاثة أشهر. الحقن الشهري بمقدار 1.25 ملجم أو 2.5 ملجم بيفاسيزوماب (أربعون مريضًا لكل مجموعة). تمت ملاحظة المرضى لمدة 4 أسابيع بعد الحقنة الأولى. تمت مقارنة التغيرات في كل من حدة الابصار الافضل تصحيحا وسمك البقعة الصفراء المركزية والآثار الجانبية للعقار في كلتا المجموعتين. انخفض بشكل ملحوظ سمك البقعة الصفراء المركزية في كلتا المجموعتين.(P<0.013) تحسينات كبيرة بين بداية الحقن والاسبوع الثاني والاسبوع الرابع في المجموعة 2.5 ملغ، حيث كان متوسط الانخفاض في السماكة البقعية الصفراء المركزية (318 إلى 182). وهو ذو دلالة احصائية مهمة تحسنت حدة الأبصار المصحةة من 0.16 إلى 0.7 وهوذو دلالة إحصائية مهمة بينما لم يكن لفرق قياس ضغط العين بين المحموعتين دلالة احصائية مهمة. يعد التحسن بجرعة من الحقن داخل الجسم الزجاجي 2.5 ملغ باستجابة فعالة سريعة وآمنة للعلاج دون أي آثار جانبية عينية أو عامة.